2013
DOI: 10.1164/rccm.201205-0788oc
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between the Effects of Lifetime Asthma, Smoking, and Atopy on Fixed Airflow Obstruction in Middle Age

Abstract: Active smoking and current clinical asthma both contribute substantially to fixed AO in middle age, especially among those with atopy. The interaction between these factors provides another compelling reason for atopic individuals with current asthma who smoke to quit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 42 publications
5
94
3
1
Order By: Relevance
“…Perret and colleagues studied the interaction between current asthma, atopy and smoking in a group of middle-aged (40-44 years) subjects with fixed airflow obstruction [Perret et al 2013]. Fiftyseven percent of the cohort were ever smokers, with 9.5% having a smoking history of more than 30 pack years.…”
Section: Influence Of Smokingmentioning
confidence: 99%
“…Perret and colleagues studied the interaction between current asthma, atopy and smoking in a group of middle-aged (40-44 years) subjects with fixed airflow obstruction [Perret et al 2013]. Fiftyseven percent of the cohort were ever smokers, with 9.5% having a smoking history of more than 30 pack years.…”
Section: Influence Of Smokingmentioning
confidence: 99%
“…Menezes and Hardin reported higher mean age in ACOS patients [12,13]. Increase of prevalence with aging is thought to be related to the development of persistent airway obstruction due to inadequate treatment or ongoing insults such as smoking [14,15]. A study by Kiljander et al revealed ACOS prevalence as 27.4% in asthma patients who have a history of smoking.…”
Section: Definition and Diagnosis Of Acosmentioning
confidence: 99%
“…Three studies were published in the Journal in 2013 that focused on airway remodeling in asthma (58-60). Perret and colleagues followed up a population-based cohort after 35 years and found that those with ongoing asthma had a significant and time-dependent relationship with lack of bronchodilator responsiveness (59). Furthermore, the effects of persistent asthma on fixed airway obstruction were synergistic with smoking, but only in those with atopy.…”
Section: Pathways That Affect Airway Remodeling and Cause Fixed Airflmentioning
confidence: 99%